Investigating Al-Istihalah in the Provisions of Shariah Texts: A Study on Models of Transformation from Impure (Najis) to Pure (Halal) Substances, or Vice Versa - Miswanto, Agus; Musaffa, Muhamad Ulul Albab (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: This article discusses the models of Istihalah introduced by Islamic jurisprudential texts. The primary issue in the contemporary era revolves around the massive food industry, which necessitates the blending of various ingredients, resulting in the unclear status of the food as either halal or haram. Istihalah becomes a crucial key in the context of the food industry because it serves as both a method and a parameter for the transformation of the substance of an object, implying a change in the legal status of the object itself, either from halal to haram or vice versa. This research employs a textual and contextual approach to reconstruct Istihalah as presented in Islamic jurisprudential texts. From this study, three models of Istihalah are identified based on the nature of the substance's transformation, namely physical, chemical, and physical-chemical transformations. From the perspective of Islamic jurisprudential texts, physical transformation can occur in two patterns: (1) halal substances processed with a catalyst that is haram result in a halal product. An example of this is honey. (2) Haram (impure) substances processed with a halal catalyst transform into a halal product, such as quarantined carrion animals and tanned animal hides. Meanwhile, chemical transformation, as found in the texts, occurs in two patterns: (1) haram (impure) products processed with a halal catalyst transform into a halal product, as seen in the case of vinegar derived from fermented wine that has transformed. (2) Halal items processed with a halal facilitator change into a haram product, such as alcoholic beverages. Finally, physical-chemical transformation in Islamic jurisprudential texts takes place when raw impure materials are processed with a halal facilitator to become a halal finished product, as exemplified by products like milk from halal animals, the liver and spleen of halal animals, and musk oil (kasturi) extracted from deer.Abstrak: Artikel ini mengulas tentang model-model istihalah yang diperkenalkan oleh nash syariat. Problem utama pada era kontemporer adalah masifnya industri makanan yang mengharuskan percampuran berbagai bahan, yang mengakibatkan tidak jelasnya status makanan itu: halal atau haram. Dan istihalah menjadi kunci penting dalam konteks industri makanan karena sebagai metode dan juga parameter terhadap perubahan zat suatu benda yang berimplikasi pada perubahan status hukum benda yang bersangkutan, yaitu dari halal ke haram, atau sebaliknya. Penelitian ini menggunakan pendekatan tekstual dan kontekstual dalam merekonstruksi istihalah yang tersaji dalam nash syariat. Dan dari penelitian ini ditemukan tiga model istihalah berdasarkan pada sifat perubahan pada benda, yaitu perubahan fisik, kimiawi, dan fisik-kimiawi.  Dari sisi nash syariat, perubahan fisik dapat terjadi dengan dua pola, yaitu (1) bahan halal diproses dengan bahan katalisator yang haram menghasilkan produk halal. Contohnya adalah produk madu lebah. (2) bahan haram (najis) diproses dengan bahan katalisator yang halal berubah menjadi produk halal, contohnya binatang jalalah yang dikarantina dan kulit bangkai yang disamak. Sedangkan perubahan kimia, dalam nash detemukan dalam dua pola yaitu (1) produk yang haram (najis) diproses dengan katalisator yang halal berubah menjadi produk halal, seperti cuka yang berasal dari khamar yang berubah. (2) barang halal diproses dengan fasilitator yang halal berubah menjadi produk haram, contohnya produk khamar. Akhirnya, perubahan fiski-kimiawi dalam nash syariat, terjadi dengan pola barang baku haram diproses dengan fasilitator halal berubah menjadi barang jadi halal, contohnya produk susu binatang halal, hati dan limpa binatang halal, dan minyak misik (kasturi) dari rusa.